Effects of Domestic Debt on Interest Rates in Nepal - Timseena, Vishnu Prasad (Interdisciplinary Journal of Management and Social Sciences, 2021)
Domestic debt has greater implications on macroeconomic stability and growth. Domestic borrowing can lead to crowding out effect, which can lower the economic growth. In this regard, the study of interest rate effect of the domestic borrowing would be useful to the policymakers and other researchers as well. The time series techniques are used to analyze the relationship between the domestic borrowing and interest rate based on annual data for the period 1990-2020. The empirical study reveals that, despite a positive relationship between domestic borrowing and interest rate, the relationship is insignificant and very weak. This implies that increase in domestic borrowings may not result in an increase in interest rates. This is mainly on account of prevailing administered interest rate on long term bond, dominance of fiscal policy in determining the interest rate of auction, lack of investment friendly environment to private sector, high level of liquidity in the economy, information asymmetry problem and many other problems.